The Application of Islamic Educational Philosophy in Overcoming Moral Crisis - Anita Handayani Anita; Kautsar Eka Wardhana (PT. Berkah Smart Academica, 2023)
This research is motivated by the importance of implementing Islamic character-based education in addressing moral crises, emphasizing the religious character through aspects of worship, faith, and morality via religious activities. Through these religious activities, it is hoped that moral crises among children can be more easily addressed, thereby shaping better morals. Therefore, the objectives of this research are to identify various forms of moral crises in children, to understand how the implementation of Islamic-based character education addresses moral crises, to find solutions for children who do not exhibit moral changes after the implementation of Islamic-based character education, and to determine the supporting and inhibiting factors in the implementation of Islamic-based character education. This research adopts a descriptive qualitative approach with Class IV MI NW Labanan as the research object. The research subjects encompass the school principal, class teachers, religious instructors, and students. Data collection techniques employed include observation, interviews, and documentation. Data analysis involves data reduction, data presentation, and drawing conclusions. Meanwhile, data validity is tested using triangulation techniques